Acoustic Analysis of Speech through a Hearing Aid: Consonant-Vowel Ratio Effects with Two-Channel Compression Amplification - Hickson, Louise; Thyer, Nick; Bates, Dianne (Journal of the American Academy of Audiology, 1999)
In this study, the consonant-vowel ratio (CVR) changes associated with varying the compression ratio and crossover frequency of two-channel syllabic compression amplification were examined. Consonant-vowel syllables were recorded at 60 and 75 dB SPL input levels to the hearing aid under 13 different amplification conditions: 12 compression conditions and a condition that used linear amplification in both channels. Syllables consisted of voiceless stops, fricatives, and affricates combined with the vowels /a/, /i/, and /u/. Acoustic analysis of the processed syllables indicated that the CVR was generally increased with compression, compared to linear amplification, and that the effects were greatest for amplification with compression in the high-frequency channel. In addition, higher CVRs were obtained when the crossover frequency was raised. Compression in the low-frequency channel had the least effect on CVR. As previous research has indicated that CVR may serve as a cue to the perception of some consonant sounds by people with hearing impairment, the results suggest the need for caution with the application of high-frequency channel compression until the perceptual effects are fully investigated.Abbreviations: CR = compression ratio, CVR = consonant-vowel ratio, rms = root mean square
Keywords: Acoustic analysis; amplification; compression; consonant-vowel ratio